Best Periodic Proximity Points for Cyclic Weaker Meir-Keeler Contractions. (31st May 2012) - Chen, Chiming; Lin, Chingju
Abstract : The purpose of this paper is to present the existence of the best period proximity point for cyclic weaker Meir-Keeler contractions and asymptotic cyclic weaker Meir-Keeler contractions in metric spaces.